Vaginal endometrial stromal sarcoma: A literature review. (October 2019) - Wu, Hongwen; Luo, Yi; Yin, Nanlin; Gui, Wenwu; Cao, Yi
Abstract: Vaginal endometrial stromal sarcoma (VESS) is a rare disease. To the best of our knowledge, there have only been a few reported cases in the literature. Therefore, we conducted a literature review to obtain specific knowledge of this disease. Thirteen cases of VESS were found by searching the Medline and EMBASE databases in the English language. The mechanism of VESS may be associated with endometriosis, and its diagnosis largely depends on pathological examination because it has no typical symptoms. Treatment of VESS incorporates surgery, chemotherapy, radiotherapy, and hormonal therapy. Some novel drugs targeting its mechanism may become alternative therapies. Its prognostic factors may include tumor stage and the expression of hormonal receptors.